2022
DOI: 10.1186/s13064-022-00163-7
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA-seq analysis reveals temporally-regulated and quiescence-regulated gene expression in Drosophila larval neuroblasts

Abstract: The mechanisms that generate neural diversity during development remains largely unknown. Here, we use scRNA-seq methodology to discover new features of the Drosophila larval CNS across several key developmental timepoints. We identify multiple progenitor subtypes – both stem cell-like neuroblasts and intermediate progenitors – that change gene expression across larval development, and report on new candidate markers for each class of progenitors. We identify a pool of quiescent neuroblasts in newly hatched la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 116 publications
0
34
0
Order By: Relevance
“…g. Pal2 42 , GABA-B-R2 43 ) . Reanalysis of recent scRNA-seq data for the Drosophila larval brain 39 confirmed that these MRG15-enriched genes were silent in NSCs and broadly expressed across mature neuron subtypes (Fig. 5d).…”
Section: Eight Principal Chromatin States Organise the Fly Genomementioning
confidence: 63%
See 4 more Smart Citations
“…g. Pal2 42 , GABA-B-R2 43 ) . Reanalysis of recent scRNA-seq data for the Drosophila larval brain 39 confirmed that these MRG15-enriched genes were silent in NSCs and broadly expressed across mature neuron subtypes (Fig. 5d).…”
Section: Eight Principal Chromatin States Organise the Fly Genomementioning
confidence: 63%
“…These compartments can be further divided into sub-compartments, partially separated by histone modifications 46 , and we wondered whether TADs of similar chromatin state would also exhibit longrange associations within the 3D genome. Reprocessing existing HiC 47 and Lamin B binding Although not significantly enriched for specific ontologies, investigation of the highest-ranking genes transitioning from Yellow-R in NSCs to Yellow states in neurons revealed a number of genes involved in synaptic structure and signalling, with scRNA-seq data (reanalysed from 39 ) confirming the change in expression status between cell types (d).…”
Section: Chromatin States Compartmentalise the 3d Genomementioning
confidence: 86%
See 3 more Smart Citations